2020
DOI: 10.5380/dma.v55i0.73174
|View full text |Cite
|
Sign up to set email alerts
|

Challenges to balance food demand and supply: analysis of PNAE execution in one semiarid region of Brazil

Abstract: This study intended to address the challenges faced by the National School Feeding Program (PNAE) to implement public purchases from family farming, as they understand their role in the transformation of local food systems. For this, we developed a qualitative, exploratory, and descriptive study, in the state of Rio Grande do Norte, located in the northeastern semiarid region, during the regional assessments done by the Collaborating Center for the School Feeding Program in 2018 and 2019. We analyzed the polic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 17 publications
(36 reference statements)
0
5
0
2
Order By: Relevance
“…Nutritionists and others involved with school management play a key role in managing public food procurement in the school environment. In addition to price surveys in local markets to allow for fair participation of family farmers in the bidding process, the menus must also be planned to consider the local products available, as well as the production practices by the farmer, considering frequency and seasonality in view of the different dynamics among large, medium, and small supply centers [23]. The public notices also need to describe the specifications of the products as a preventative measure in food purchases to ensure proper hygienic-sanitary conditions, even to allow for impartial analysis of food samples that are part of one of the steps of the food procurement processes [54].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nutritionists and others involved with school management play a key role in managing public food procurement in the school environment. In addition to price surveys in local markets to allow for fair participation of family farmers in the bidding process, the menus must also be planned to consider the local products available, as well as the production practices by the farmer, considering frequency and seasonality in view of the different dynamics among large, medium, and small supply centers [23]. The public notices also need to describe the specifications of the products as a preventative measure in food purchases to ensure proper hygienic-sanitary conditions, even to allow for impartial analysis of food samples that are part of one of the steps of the food procurement processes [54].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have revealed that although family farming is a significant part in a number of agricultural establishments, it lacks in area of hectares (many are not even proprietors of their cultivation land), in structures, and incentives that allow their development and expansion as producers, and shows to be vulnerable in matters of soil and climate (such as the droughts in certain regions of the northeast, as RN), while, in contrast, large retail and corporate producers are strengthened [4,23,39]. In addition to political-administrative issues of the sectors involved, some products require sanitary and normative quality standards and criteria of specific verification that end up hindering the inclusion of those farmers in such a commercial sector [56].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…O Brasil tem um programa de alimentação escolar que é referência no mundo, o Programa Nacional de Alimentação Escolar (PNAE), que atende 40 milhões de crianças em todo o país (Chaves et al, 2020). A lei nº 11.947, de 16 de junho de 2009 determina a compra de no mínimo 30% do valor repassado de gêneros alimentícios diretamente da agricultura familiar local, do empreendedor familiar rural local ou de suas organizações (Amorim et al, 2020).…”
Section: Discussão Geralunclassified
“…No entanto, nem todas as cidades conseguem atender essa quantidade mínima. Na região Nordeste, por exemplo, em média as compras são de 20% do total do valor repassado e a incapacidade de produção, distribuição e armazenamento do produtor rural são parte do problema (Chaves et al, 2020). A fermentação ácido lática pode ser uma ferramenta importante para a agricultura familiar para esta finalidade já que, mas não apenas, é um processo de preservação de alimentos.…”
Section: Discussão Geralunclassified